Multifunctional and flexible ZrO2-coated EGaIn nanoparticles for photothermal therapy. Issue 21 (21st May 2019) - Xia, Na; Li, Na; Rao, Wei; Yu, Jie; Wu, Qiong; Tan, Longfei; Li, Hongbo; Gou, Li; Liang, Ping; Li, Laifeng; Meng, Xianwei
Abstract : The nanoparticle not only formed a stable core–shell LM structure, but also maintained the ideal flexibility of the LM. Abstract : With extensive investigations involving liquid metals (LMs), Ga-based LMs have attracted increasing attention from biomedical researchers because of their good biocompatibility, ideal fluidity, and high thermal conductivity. LMs employed in cancer treatment suffer from high surface tension, thereby yielding unstable nanoparticles (NPs). Here, ZrO2 is coated onto LM NPs to form a stable core–shell nanostructure. In particular, LM NPs coated with ZrO2 and modified by PEG (LM@pZrO2 NPs) still maintain favorable flexibility, which is beneficial for cellular uptake. With regard to the photothermal properties of LM, LM@pZrO2 NPs rapidly warm up and emit the requisite amount of heat under NIR laser radiation. It is confirmed that LM@pZrO2 NPs are more effectively internalized by cells and are beneficial for tumor photothermal therapy. This research provides a coating strategy to fabricate a stable and flexible core–shell LM nanostructure, making it a promising vehicle for nanotheranostics.